Reviews and Responses for Very-low-level U-space Conflict Detection and Resolution: Current Developments and Future Prospects - Badea, Calin Andrei; Morfin Veytia, Andres; Vidosavljević, Andrija; Ellerbroek, Joost; Hoekstra, Jacco; Chen, Shulu; Conrad, Christopher; Chen, Yutong (Journal of Open Aviation Science, 2025)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2025.7921